Training and Mentoring on Best Practice Writing Based on Creative and Innovative Learning for Teachers - Ida Ayu Made Wedasuwari; Teguh Alfaidzin; Duratul Nadhirah; Eka Yudi Tama (Al-Qalam Institute, 2026)
This community service program aimed to enhance teachers’ competencies in writing best practices based on creative and innovative learning experiences. Many teachers encountered difficulties in systematically documenting innovative instructional practices due to limited academic writing skills and the absence of structured mentoring. The program employed a participatory training and mentoring approach consisting of five stages: identification of teachers’ needs, program preparation, training implementation, evaluation, and continuous mentoring. Data were collected through observations, questionnaires, and pretest-posttest assessments to measure participants’ understanding and writing abilities. The findings revealed a significant improvement in teachers’ competencies, as indicated by a 9.32% increase in pretest and posttest scores. In addition, participants demonstrated greater confidence and motivation in documenting and disseminating their innovative teaching experiences in written form. The program implies that systematic training and mentoring in best practice writing can strengthen teachers’ professional competencies, promote reflective teaching practices, and encourage the broader dissemination of innovative learning models in educational settings.